2014
DOI: 10.1016/j.exger.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Chronic CMV infection in older women: Longitudinal comparisons of CMV DNA in peripheral monocytes, anti-CMV IgG titers, serum IL-6 levels, and CMV pp65 (NLV)-specific CD8+ T-cell frequencies with twelve year follow-up

Abstract: Chronic cytomegalovirus (CMV) infection may contribute significantly to T-cell immunosenescence, chronic inflammation, and adverse health outcomes in older adults. Recent studies suggest detectable CMV DNA in peripheral monocytes as a better indicator for this persistent viral infection than anti-CMV IgG serology. Here, we conducted longitudinal comparisons of anti-CMV IgG titers, CMV DNA in the peripheral monocytes, serum IL-6 levels, and CMV pp65 (NLV)-specific CD8+ T-cell frequencies in fifteen community-dw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 32 publications
2
28
1
Order By: Relevance
“…15,36,[41][42][43][44] Our study provides the first demonstration of a strong relationship between CMV IgG and impaired physical function in HIV infection. Whether CMV alone plays a causative role in the deterioration of physical function or is a marker of another variable that is associated with decreased physical function could not be determined in this study.…”
Section: Cd38mentioning
confidence: 60%
See 1 more Smart Citation
“…15,36,[41][42][43][44] Our study provides the first demonstration of a strong relationship between CMV IgG and impaired physical function in HIV infection. Whether CMV alone plays a causative role in the deterioration of physical function or is a marker of another variable that is associated with decreased physical function could not be determined in this study.…”
Section: Cd38mentioning
confidence: 60%
“…34,35 It should also be noted that a small study of HIV-infected persons found that detectable CMV DNA was negatively correlated with CMV IgG 17 and among 12 HIV-uninfected CMV-seropositive women from the Women's Health and Aging Study, CMV IgG titers were minimally different between two time points 12 years apart, despite detectable CMV DNA at both time points in seven participants. 36 Furthermore, CMV cell-mediated immune responses to the pp65 peptide pool may underestimate total T cell responses against CMV. 37 Thus, the reason for discordance between cellmediated and humoral responses in our HIV-infected participants cannot be entirely explained and further investigation is needed.…”
Section: Cd38mentioning
confidence: 99%
“…Interestingly, scarce attention has been devoted to the relationship between 25(OH)D and IL-6. This is surprising because IL-6 is the primary biomarker of phenotypes of aging, underlying not detected conditions (Li et al 2014) and adverse outcomes, including disability and death (Maggio et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We have developed and optimized a nested PCR-based assay for HCMV DNA detection in the peripheral blood monocytes from older adults. Our data from cross-sectional and longitudinal studies indicate that (a) HCMV DNA in monocytes is present in only about 55-60% of HCMV-seropositive older persons, (b) this subset has high HCMV pp65-specific CD8 + T cell frequencies and elevated serum levels of IL-6 (chronic inflammation) and neopterin (immune activation) relative to CMVseropositive persons with no HCMV DNA in the peripheral blood monocytes, and (c) gain or loss of HCMV DNA in monocytes is closely associated with increases or decreases, respectively, in HCMV-specific CD8 + T cells and IL-6 levels, even when anti-HCMV IgG titers do not change appreciably (Leng et al 2011b;Leng et al 2011a;Li et al 2014b). Consistent with these results, one study employing digital droplet PCR (ddPCR) also reported the utility of HCMV DNA detection in the peripheral blood monocytes for the evaluation of latent/chronic HCMV infection in older adults (Parry et al 2016).…”
Section: Chronic CMV Infection In Older Adults: Diagnostic Evaluationmentioning
confidence: 99%